Investigation on characteristics and performance of bearing spacer ring - Guo, Jiang; Zhao, Yong; Long, Pengyu; Wang, Jinglin; Du, Benyu; Rajpar, Bilal Mustafa; Jin, Zhuji; Tang, Jiwu (Frontiers in Materials, 2023)
Bearings are widely used in the industry due to their ability to support the movement of rotating bodies. The spacer rings are a key component of double-row roller bearings; therefore, the characteristics and properties of the spacer rings have a significant impact on the bearing functions. However, the lack of the characteristics and performance analysis of the spacer ring limits the improvement of bearing performance. To analyze the characteristics of spacer rings and establish a basis for improving their performance, a new testing method for the characteristics and performance of the spacer ring was presented and corresponding experiments were developed. The test procedure entails the evaluation of basic characteristics, surface properties, and serviceability. Basic characteristics were determined through element testing and cross-section morphological observation; surface properties were assessed through surface morphology and surface roughness detection; and serviceability was identified by cross-section hardness and frictional wear tests. The results show that the proposed test method can comprehensively characterize the performance of the spacer rings. The spacer ring composition mainly contains Fe, Al, P, Si, Ca, and S, which contribute to excellent wear resistance, hardness, strength, and corrosion resistance. The cross-sectional morphology exhibits porous characteristics, which enhance lubricity. In terms of surface property, the surface of the spacer ring is relatively flat, and the surface roughness is generally less than 0.6 μm Sa. The average friction coefficient is 0.85, and the friction and wear properties of the spacer ring are good. This study contributes to establishing the testing and evaluation criteria for the performance of spacer rings in engineering, which helps to improve the performance of bearings.